2021
DOI: 10.1007/s00432-020-03504-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of rapid reduction of involved free light chains in multiple myeloma patients under first-line treatment with Bendamustine, Prednisone, and Bortezomib (BPV)

Abstract: Introduction Light chain involvement is observed in almost every patient (pt) with newly diagnosed multiple myeloma (MM). Owing to a relatively short half-life, rapid reduction in the involved free light chain (iFLC) is of potential prognostic value. Methods This retrospective analysis included 92 pts with newly diagnosed MM treated with bendamustine, prednisone, and bortezomib (BPV). Results After a median number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Our data indicate that early assessment of sFLCs as early as cycle 1 has a significant impact on prognosis. Our results are also consistent with Holzhey et al who demonstrated that rapid sFLC decrease on day 8 is an early prognostic marker for newly diagnosed patients undergoing bortezomib-based treatments [ 10 ].…”
supporting
confidence: 92%
“…Our data indicate that early assessment of sFLCs as early as cycle 1 has a significant impact on prognosis. Our results are also consistent with Holzhey et al who demonstrated that rapid sFLC decrease on day 8 is an early prognostic marker for newly diagnosed patients undergoing bortezomib-based treatments [ 10 ].…”
supporting
confidence: 92%
“…While the EuLITE study did not achieve any bene t in terms of dialysis independence, a French study using HCO-HD reported a signi cantly higher rate of hemodialysis independency after 6-12 months (Bridoux et al 2017; Hutchison et al 2019). Using induction therapy with BPV, our study group has also demonstrated a similarily rapid reduction in involved free light chain within the rst week of treatment in the majority of MM patients (Holzhey et al 2021). In the present study, we observed a favorable renal response rate of 61% after BPV induction, comparable to those observed for other regimes containing novel agents (Dimopoulos et al 2016).…”
Section: Discussionmentioning
confidence: 56%
“…The majority of patients with severe renal dysfunction or renal failure/dialysis received an induction treatment with BPV. As induction therapy, this combination has shown high efficacy and good tolerability in both transplant-eligible and non-transplant-eligible MM patients with renal impairment (Pönisch et al 2014 ; Poenisch et al 2015 ; Holzhey et al 2021 ). Specifically, this combination induced a rapid reduction in monoclonal LC production in the first few days of treatment, potentially preventing the development of irreversible renal failure (Pönisch et al 2015; Tessenow et al 2017 ; Holzhey et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…As induction therapy, this combination has shown high efficacy and good tolerability in both transplant-eligible and non-transplant-eligible MM patients with renal impairment (Pönisch et al 2014 ; Poenisch et al 2015 ; Holzhey et al 2021 ). Specifically, this combination induced a rapid reduction in monoclonal LC production in the first few days of treatment, potentially preventing the development of irreversible renal failure (Pönisch et al 2015; Tessenow et al 2017 ; Holzhey et al 2021 ). The German-Speaking Myeloma Multicenter Group (GMMG) previously reported that the bortezomib-based triplet therapy PAD before ASCT could overcome the negative prognostic impact of renal impairment (Scheid et al 2014 ).…”
Section: Discussionmentioning
confidence: 99%